Comparisons of a chicken-based formula with soy-based formula in infants with cow milk allergy - Pipop Jirapinyo (2018)
Objective: To determine whether chicken-based formula can replace soy-based formula in infants with cow milk allergy. Subjects and Methods: Thirty-eight infants with cow's milk allergy, aged between 2-24 months of age were randomized to receive either chicken-based formula or soy-based formula for 14 days. Results: In the group of soy-based formula, 12 out of 18 infants had evidence of intolerance and could not continue with the formula. However, only 4 out of 20 infants in the chicken-based formula group had evidence of clinical intolerance. All other 16 infants were fed the chicken-based formula with success. The number of infants who were intolerant to chicken formula was significantly lower than the number of those fed soy-based formula (p = 0.009). Conclusion: Chicken-based formula can be used more effectively than soy-based formula in infants with cow milk allergy.